Numerical Simulation of the Influence of Geometric Configurations on Pressure Difference in the Intraventricular Tunnel - Yang, Yao; Wang, Junjie; Qiao, Aike; Fan, Xiangming (Frontiers in Physiology, 2020)
Objective The geometric configuration of the intraventricular tunnel (IVT) is related to the re-intervention of left ventricular outflow tract stenosis after double outlet right ventricle (DORV) correction. Hemodynamic simulation was performed to study the influence of the geometric configuration of IVT on the flow resistance. Methods CT images of DORV were processed to determine the size and relative position of the aortic valve orifice and ventricular septal defect. Nine groups of the idealized IVT models were established according to orthogonal test design and computational fluid dynamics method was applied to simulate hemodynamics. Three factors of geometric configuration were considered for the study of their influences on the flow resistance. One factor is the distance between the ventricular septal defect and the plane of the aortic valve (DSA), the second factor is the ejection angle of blood from left ventricle flowing into the IVT (ALT), and the third factor is the turning radius of the IVT (RTT). SPSS software was employed to perform the orthogonal analysis. Additionally, twelve models with different turning radii were established for hemodynamic analysis, with the turning radii increasing from 0 mm with an interval of 1 mm, so as to study the influence of turning radius on flow resistance of IVT. Results The analysis of variance showed that only the change of RTT had a significant effect on the flow resistance (P=0.024<0.05), while the change of DSA and ALT had no significant effect on the flow resistance (P=0.665>0.05, P=0.269>0.05). The flow resistance decreases with the increase of RTT. When RTT reaches 6 mm, the flow resistance gradually remains unchanged with the increase of RTT, and the rate of change is less than 5%. Conclusion RTT in the IVT is the main factor affecting the flow resistance. A small RTT will lead to a large flow resistance in the IVT. When RTT increases to 6 mm, the flow resistance in the IVT remains nearly unchanged. When performing the right ventricular double outlet correction; the turning radius of the IVT should be about 6 mm to ensure relatively small flow resistance.